Conceitos de eletricidade e suas aplicações tecnológicas : uma unidade de ensino potencialmente significativa - Lopes, Ricardo Rodrigo Silva (2014)
The main objective of this project was developing a teaching unit on concepts of electricity and validating it as a Potentially Meaningful Teaching Unit (PMTU). To accomplish it, it was created a instruction unit based on the Theory of Meaningful Learning of Ausubel related to topics of Physics, such as, difference of potential, electric current and its applications. That unit was applied in six classes of the third year of a public high school of the state of Espírito Santo. In order to investigate the potential of this method of teaching, it was used descriptive qualitative research methodologies and pre-experimental interpretative quantitative. In the beginning of the study, to collect students’ prior knowledge, students were asked to answer opinion questionnaires, previous dialogues were recorded and conceptual maps were built. They were important instruments to gather information about the instructional material and they enabled to make improvements on it to be suitable to the profile and cognitive structure of students. Besides, audio recordings of the main parts, logbooks, pictures about students working, panels made by students, questionnaires, conceptual maps and the written assessment, were used as source of data. Conceptual maps analyses, constitute one of the main tools for evaluation the didactic sequence according to the cognitive development of students, in order to classify the maps, associate them with the cognitive structures of those who built them and identify valid changes related to buildings new meanings. The investigation revealed that, in general, the teaching unit was responsible for significant improvements in students' disposition to learn and in stimulating meaningful learning, enabling the validation of this PMTU.